8C.08: CONTINUOUS POSITIVE AIRWAY PRESSURE IS EFFICIENT TO DECREASE BLOOD PRESSURE IN PATIENTS WITH RESISTANT HYPERTENSION. RESULTS FROM THE RHOOSAS STUDY. (June 2015) - Baguet, J. P.; Sosner, P.; Delsart, P.; Jost, S.; Tamisier, R.; Pepin, J.L.
Abstract : Objective: Most of patients suffering from resistant hypertension (HTN) have obstructive sleep apnea (OSA). Little data are available to confirm or not the efficacy of continuous positive airway pressure (CPAP) on blood pressure (BP) in resistant HTN. Design and method: We performed a multicentric, comparative (presence or not of OSA), randomized (sham CPAP then active CPAP versus active CPAP right away), simple blind study in patients with essential resistant HTN (confirmed by ABPM). OSA patients (apnea-hypopnea index, AHI, > 15 per hour) previously untreated for OSA received CPAP. Follow-up was of 6 (active CPAP group) or 9 (sham CPAP group) months. Results: 61 patients were included, mean age 59.6 years, 77% of men, BMI 29.6 kg/m 2, daytime BP 145/85 mmHg, 3.7 antihypertensive drugs. The 36 OSA patients (59%, mean AHI 44.8) were predominantly men (86 vs 64%, p = 0.043), with metabolic syndrome (83 vs 60%, p = 0.042). After a period of 6 months under active CPAP, BP decreased by 3.4 (p = 0.161) and 2.8 (p = 0.068) mmHg over 24 hours, by 1.6 (ns) and 1.9 (ns) mmHg during the day and by 5.5 (p = 0.022) and 4.0 (p = 0.015) mmHg during the night, respectively for systolic and diastolic BP. Dipper profile was improved by active CPAP (64.5 vs 35.5 %, p = 0.047, for systolic BP, and 71 vs 58%, p = 0.084, for diastolic BP). Conclusions: Not only OSA must be investigated in resistant HTN but also its treatment must be started. Indeed, besides its interest on sleepiness, CPAP is efficient to decrease nighttime BP in apneic patients suffering from resistant HTN. This explains in part the benefit of CPAP on morbidity-mortality of OSA patients.